Potential benefits of tanniferous forages in integrative crop-livestock agroecosystems - Clemensen, Andrea; Halvorson, Jonathan J.; Christensen, Rachael; Kronberg, Scott L. (Frontiers in Agronomy, 2022)
Integrating livestock into cropping systems may enhance ecosystem services while still providing efficient food production. Including tanniferous forages in crop-livestock systems could further enhance ecosystem services. Interest in phytochemicals, such as tannins, has increased over the past several decades, and research continues to reveal the potential benefits of tannins in agricultural systems. However, research evaluating the influence of tanniferous forages in integrative crop-livestock systems is limited. We discuss how tannins influence soil microbial dynamics and nutrient cycling, the function of tannins in forages, and the role tannins have in improving the health of foraging animals. We speculate on potential advantages for human health from consumption of animal-based foods from animals that consumed tanniferous forages or supplemental plant materials. Expanding our knowledge and integration of phytochemicals in muti-faceted agroecosystem research and utilizing their influence in agriculture system dynamics may be an effective tool to enhance agroecological sustainability.